Analyzing Malaysian consumers' decision making styles dimensions in banking services - Zainal Ariffin, Zailin (2002)
The greater globalisation of the world trade will force Malaysian bankers to address the issue of how customers perceive them in comparison to their foreign competitors. The general objective for the research is to identify or investigate the decision-making style dimensions for Malaysia in banking services. Therefore, the study attempts to identify the Malaysian consumers' decision-making style dimensions in banking services. Specifically, the objectives of this research are to develop dimensions of Malaysian consumers based on their decision-making styles in banking services and to examine or determine the characteristics of consumers; group from the developed typology. A total of 545 usable questionnaires were collected and analysed using Statistical Packages For Social Sciences (SPSS) version 10.0. The data analysis processed in four steps i.e. descriptive analysis, inferential analysis, factor analysis and reliability test. The 33 - items were used as input for factor analysis and a ten-factor solution was obtained with 55.464 percent of variance explained. Seven of the ten dimensions have been confirmed by reliability analysis. These seven dimensions are "habitual and quality conscious" consumers, "convenience" conscious consumer, "service' features" conscious consumer, "novelty and quality" conscious consumer, "habitual, brand loyal" consumers, "confused by other choice" consumers and "price equals quality" consumers. The other three decision making dimensions, they are "value for money" consumers, "conventional" consumers and "price" conscious consumers were not included because of their unreliable outcome in alpha test. The dimensions of decision-making style in banking services in Malaysia were identified and classified. The most crucial is that the new area has been explored in decision-making style for service category. As the study confirmed seven dimensions of consumer decision making styles and added more evidence to this framework that can be used to develop better consumer decision making guidelines in consumer's buying decision.